Anthropomorphism (Tashbīh) in the Qur’an: A Thematic Study of Tafsir Marah Labid by Al-Nawawi al-Bantani - Yudha, Muhammad Aga (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
The concept of anthropomorphism (tashbīh) as a method of understanding divinity is explicitly rejected in the Qur'an. However, since the Qur'an is revealed in human language, discussions about divine attributes inevitably employ expressions familiar to its audience. This creates a need for a comprehensive academic inquiry into how the Qur'an addresses and rejects anthropomorphic depictions of God. This study aims to explore the meaning and dimensions of tashbīh in the Qur'an based on a thematic analysis of Tafsir Marāḥ al-Labīd by Shaikh Nawawi al-Jāwī. The research employs a qualitative thematic method by collecting and analyzing relevant verses along with Nawawi’s exegetical insights and supporting theological references. The findings reveal that Shaikh Nawawi classifies tashbīh into three distinct categories. Understanding these categories requires specific interpretive principles (ḍawābiṭ), including: (1) similarity in wording does not imply similarity in essence; (2) resemblance in non-actual realities (amr ʿadamī) does not constitute tashbīh; and (3) the subject of comparison (mushabbah) may share attributes or functions with its counterpart (mushabbah bih) without implying equivalence. This study concludes that Marāḥ al-Labīd presents a nuanced theological and linguistic perspective on anthropomorphic expressions, reinforcing the transcendence (tanzīh) of God in Islamic thought. The research contributes to Qur'anic studies by clarifying the interpretive boundaries between metaphorical language and theological orthodoxy.